Fish Fingerprinting: Identifying Crude Oil Pollutants using Bicyclic Sesquiterpanes (Bicyclanes) in the Tissues of Exposed Fish. (18th November 2022) - Spilsbury, Francis D.; Scarlett, Alan G.; Rowland, Steven J.; Nelson, Robert K.; Spaak, Gemma; Grice, Kliti; Gagnon, Marthe Monique
Abstract: In the present study, we investigated the possibility of identifying the source oils of exposed fish using ratios of bicyclic sesquiterpane (bicyclane) chemical biomarkers. In the event of an oil spill, identification of source oil(s) for assessment, or for litigation purposes, typically uses diagnostic ratios of chemical biomarkers to produce characteristic oil "fingerprints." Although this has been applied in identifying oil residues in sediments, water, and sessile filtering organisms, so far as we are aware this has never been successfully demonstrated for oil‐exposed fish. In a 35‐day laboratory trial, juvenile Lates calcarifer (barramundi or Asian seabass) were exposed, via the diet (1% w/w), to either a heavy fuel oil or to Montara, an Australian medium crude oil. Two‐dimensional gas chromatography with high‐resolution mass spectrometry and gas chromatography–mass spectrometry were then used to measure selected ratios of the bicyclanes to examine whether the ratios were statistically reproducibly conserved in the fish tissues. Six diagnostic bicyclane ratios showed high correlation ( r 2  > 0.98) with those of each of the two source oils. A linear discriminatory analysis model showed that nine different petroleum products could be reproducibly discriminated using these bicyclane ratios. The model was then used to correctly identify the bicyclane profiles of each of the two exposure oils in the adipose tissue extracts of each of the 18 fish fed oil‐enriched diets. From our initial study, bicyclane biomarkers appear to show good potential for providing reliable forensic fingerprints of the sources of oil contamination of exposed fish. Further research is needed to investigate the minimum exposure times required for bicyclane bioaccumulation to achieve detectable concentrations in fish adipose tissues and to determine bicyclane depuration rates once exposure to oil has ceased. Environ Toxicol Chem 2023;42:7–18. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.